2022
DOI: 10.1001/jamasurg.2021.5246
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of LGBTQ+ Residents in US General Surgery Training Programs

Abstract: IMPORTANCE Previous studies have shown high rates of mistreatment among US general surgery residents, leading to poor well-being. Lesbian, gay, bisexual, transgender, queer, and other sexual and gender minority (LGBTQ+) residents represent a high-risk group for mistreatment; however, their experience in general surgery programs is largely unexplored. OBJECTIVE To determine the national prevalence of mistreatment and poor well-being for LGBTQ+ surgery residents compared with their non-LGBTQ+ peers. DESIGN, SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 47 publications
0
75
0
Order By: Relevance
“…These diverging trajectories may reflect additional stressors sexual minority physicians face, including high rates of harassment and discrimination and a lower sense of belonging, and may contribute to disparities in burnout, suicidal thoughts, and attrition. 2 , 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These diverging trajectories may reflect additional stressors sexual minority physicians face, including high rates of harassment and discrimination and a lower sense of belonging, and may contribute to disparities in burnout, suicidal thoughts, and attrition. 2 , 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…Although sexual minority trainees experience higher rates of mistreatment and other unique stressors, little is known about their mental health. 2 , 3 , 4 , 5 Here, we assess the prevalence and development of depressive symptoms among sexual minority and heterosexual physicians over the course of residency training.…”
Section: Introductionmentioning
confidence: 99%
“…9 Additionally, a substantial amount of LGBTQIA+ residents experience discrimination and mistreatment from both patients and other health care providers, highlighting a critical structural need to boost diversity, equity, and inclusion. [31][32][33] Although most program directors desire inclusion of sexual and gender minority-adjacent curricula, few emergency medicine residencies have incorporated LGBTQIA+ health into their conference and didactic curricula. 9…”
Section: Studentsmentioning
confidence: 99%
“…A 2014 study reported a median of 45 min of LGBTQIA+ content in EM didactics, and a related study in 2018 found that a significant proportion of EM residents felt less comfortable caring for LGBTQIA+ patients when compared to cisgender and heterosexual patients 9 . Additionally, a substantial amount of LGBTQIA+ residents experience discrimination and mistreatment from both patients and other health care providers, highlighting a critical structural need to boost diversity, equity, and inclusion 31‐33 . Although most program directors desire inclusion of sexual and gender minority–adjacent curricula, few emergency medicine residencies have incorporated LGBTQIA+ health into their conference and didactic curricula 9 …”
Section: Introductionmentioning
confidence: 99%
“…Lesbian, gay, bisexual, transgender, queer, and other sexual and gender minority (LGBTQIA+) health care workers experience harassment, discrimination, and mistreatment. 1 , 2 , 3 Although approximately 1.2% of matriculating medical students in 2021 identified as transgender and/or gender expansive (TGE; gender expansive is an umbrella term encompassing individuals and gender identities that may exist beyond the binary framework [eg, may include nonbinary, genderqueer, and agender individuals]), there is a paucity of understanding of the experiences of TGE physicians, as most studies include few to no TGE individuals (glossary of terms in eTable 1 in the Supplement ). 4 One 2019 survey of 36 TGE medical students and physicians found that 50% experienced barriers attributed to their gender identity when applying for jobs.…”
Section: Introductionmentioning
confidence: 99%